The Analysis of the Teacher-Made Multiple-Choice Tests Quality for English Subject - Indrayani, M.S.D,; Marhaeini, A.A.I.N,; Paramartha, A.A.G.Y,; Wahyuni, L.G.E, (LPPM Undiksha, 2020)
This study aimed at investigating and analyze the quality of teacher-made multiple-choice tests used as summative assessment for English subject. The quality of the tests was seen from the norms in constructing a good multiple-choice test. The research design used was descriptive research. Document study and interview were used as methods of collecting the data. The data was analyzed by comparing the 18 norms in constructing a good multiple-choice test and the multiple-choice tests, then, analyzed by using formula suggested by Nurkencana. The result showed the quality of the teacher-made multiple-choice tests a is very good with 79 items (99%) qualified as very good and I item (1%) qualified good. There were still found some problems referring to some norms. Therefore, it is suggested that the teachers have to pay attention to these unfulfilled norms. To minimize the issues, it is further suggested to do peer review, rechecking, and editing process.